Functional imaging early during (chemo)radiotherapy for response prediction in head and neck squamous cell carcinoma; a systematic review. (January 2019) - Martens, Roland M.; Noij, Daniel P.; Ali, Meedie; Koopman, Thomas; Marcus, J. Tim; Vergeer, Marije R.; de Vet, Henrica; de Jong, Marcus C.; Leemans, C. René; Hoekstra, Otto S.; de Bree, Remco; de Graaf, Pim; et al.
Highlights: HNSCC showed prognostic changes in perfusion, diffusion and metabolic activity. Intratreatment decrease of diffusion restriction (increase ADCmean) predicted LRC. A low intratreatment SUVmax (low 18F-FDG uptake) were predictive of LRC. A low SUVmax and total lesion glycolysis (TLG) predicted favorable OS. Best timing for imaging predicting LRC or OS is 2–3 weeks after start treatment. Abstract: This systematic review gives an extensive overview of the current state of functional imaging during (chemo)radiotherapy to predict locoregional control (LRC) and overall survival (OS) for head and neck squamous cell carcinoma. MEDLINE and EMBASE were searched for literature until April 2018 assessing the predictive performance of functional imaging (computed tomography perfusion (CTp), MRI and positron-emission tomography (PET)) within 4 weeks after (chemo)radiotherapy initiation. Fifty-two studies (CTp: n = 4, MRI: n = 19, PET: n = 26, MRI/PET: n = 3) were included involving 1623 patients. Prognostic information was extracted according the PRISMA protocol. Pooled estimation and subgroup analyses were performed for comparable parameters and outcome. However, the heterogeneity of included studies limited the possibility for comparison. Early tumoral changes from (chemo)radiotherapy can be captured by functional MRI and 18 F-FDG-PET and could allow for personalized treatment adaptation. Lesions showed potentially prognostic intratreatment changes in perfusion, diffusion and metabolic activity. Intratreatment ADCmean increase (decrease of diffusion restriction) and low SUVmax (persistent low or decrease of 18 F-FDG uptake) were most predictive of LRC. Intratreatment persistent high or increase of perfusion on CT/MRI (i.e. blood flow, volume, permeability) also predicted LRC. Low SUVmax and total lesion glycolysis (TLG) predicted favorable OS. The optimal timing to perform functional imaging to predict LRC or OS was 2–3 weeks after treatment initiation.